Answer :

It is given that equation of curve is x = cost, y = sint



On differentiating with respect to x, we get




Therefore, the slope of the tangent at ) is -1.


When


Then, the equation of the tangent is is


y – = -1(x – )


x + y -- = 0


x + y - = 0


Then, slope of normal at


=


Now, equation of the normal at


y – = 1(x –)


x = y


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the equationRD Sharma - Volume 1

Find the equationMathematics - Board Papers

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the conditioMathematics - Exemplar